缝洞型碳酸盐岩油藏三维大尺寸物理模型及其制备方法 (2023)
本发明涉及一种缝洞型碳酸盐岩油藏三维大尺寸物理模型及其制备方法，该模型是由模拟溶洞、模拟裂缝和恒温烘箱组成。该制备方法具体是通过反应釜封装经测试分析后的碳酸盐岩露头模拟溶洞，通过管线填充压实碳酸盐岩颗粒模拟裂缝；通过阀门、接头连接不同数量、不同空间位置的封装模拟溶洞和模拟裂缝，构成模拟碳酸盐岩缝洞网络结构并将其安装于恒温烘箱中，构成缝洞型碳酸盐岩三维大尺寸物理模型。本发明既能模拟缝洞型碳酸盐岩油气藏实际储层中缝洞间复杂的空间网状结构，又能反映固相储层岩石的物理、化学性质，还能模拟实际储层的高温高压条件，以及井打在不同位置时的生产效果。 The invention relates to a three-dimensional large scale physical model of a fracture-cave type carbonate reservoir and a preparation method of the three-dimensional large scale physical model. The model is composed of a simulated karst cave, a simulated fracture and a constant temperature oven. The preparation method specifically includes the steps that a carbonate rock outcrop which is tested and analyzed is sealed through a reaction still to simulate the karst cave, and a fracture is simulated through pipeline filling to press carbonate grains; valves and joints are used for connecting the sealed simulated karst caves and the simulated fractures which are in different number and different space positions, so that a simulated carbonate fract